2011
DOI: 10.1103/physrevlett.107.055501
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond Dynamics of Ferroelectric/Dielectric Superlattices

Abstract: The nanosecond response of a PbTiO(3)/SrTiO(3) ferroelectric/dielectric superlattice to applied electric fields is closely linked to the dynamics of striped domains of the remnant polarization. The intensity of domain satellite reflections observed with time-resolved x-ray microdiffraction decays in 5-100 ns depending on the magnitude of the electric field. The piezoelectric response of the superlattice within stripe domains is strongly suppressed due to electromechanical clamping between adjacent regions of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 20 publications
1
45
0
Order By: Relevance
“…The depolarization field of ultrathin layers can be screened by chemical adsorbates [12,13], charged oxygen vacancies [14], or metallic electrodes [15,16], resulting in changes in both the domain pattern and the atomic structure. Applied electric fields can similarly affect the domain pattern, including by introducing a transformation to a uniform domain configuration [10,17].…”
mentioning
confidence: 99%
“…The depolarization field of ultrathin layers can be screened by chemical adsorbates [12,13], charged oxygen vacancies [14], or metallic electrodes [15,16], resulting in changes in both the domain pattern and the atomic structure. Applied electric fields can similarly affect the domain pattern, including by introducing a transformation to a uniform domain configuration [10,17].…”
mentioning
confidence: 99%
“…While the results of the superlattices asymmetrically sandwiched between Nb-doped SrTiO 3 (bottom) and gold (top) electrodes were consistent with a monodomain configuration, 28 those corresponding to the use of symmetrically coated SrRuO 3 electrodes (both top and bottom) suggested a polydomain phase with DW motion, which dynamics might be quite different than the conventional one. 29 Furthermore, through a combination of x-ray diffraction, transmission electron microscopy, and ultrahigh resolution electron energy loss spectroscopy (EELS), Zubko et al 30,31 have also recently showed the progressive transition between two different regimes, controlled by the thickness of the individual SrTiO 3 and PbTiO 3 layers. In the first regime, present for sufficiently thin paraelectric layers, SrTiO 3 and PbTiO 3 are strongly electrostatically coupled: a uniform monodomain polarization is adopted throughout the thickness of the superlattice to minimize the depolarizing field.…”
Section: Introductionmentioning
confidence: 99%
“…The physical properties of the boundaries of the domains can differ significantly from the remainder of the material and the contribution of these nanodomain walls to the free energy can modify the response to applied fields [2] and the critical temperature of the ferroelectric-paraelectric phase transition [1]. Nanodomains in thin layers of ferroelectrics usually exhibit a serpentine-striped pattern [3,4], an indication of the complicated energy landscapes possibly arising from pinning mechanisms such as ion vacancies and structural defects. A crucial issue in the physics of ferroelectric nanodomains is to determine what effects govern the energy landscape for the reconfiguration of domain patterns because this landscape determines the stability and time-evolution of the domain pattern.…”
mentioning
confidence: 99%
“…However, it is technically challenging to image fluctuating ferroelectric nanodomain patterns directly because of a combination of the nm-scale periodicity of the domain pattern [3] and the pm-scale atomic displacements that distinguish domains with different polarization directions [9]. X-ray diffraction probes are sensitive to such small displacements but, with incoherent illumination, provide information about the ensemble average domain configuration allowing only the average parameters of the pattern to be determined [4,10].…”
mentioning
confidence: 99%